Transformasi Pendidikan di lembaga Raudlatul Athfal Strategi Menghadapi Tantangan Zaman Kekinian - Euis Trismayanti (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2025)
This qualitative case study investigates learning strategies as part of educational transformation in Raudlatul Athfal (RA) in response to the challenges of the contemporary era, characterized by rapid technological advancement, social dynamics, and 21st-century competency demands. Grounded in the constructivist theories of Piaget and Vygotsky, this research explores the implementation of child-centered learning through in-depth interviews, participant observations, and document analysis in two RA institutions located in Parigi District, Pangandaran Regency, representing both urban and semi-rural contexts. The findings reveal a significant shift from traditional approaches toward more active and contextual learning strategies, such as project-based learning, independent exploration, and collaborative activities. These approaches enhance children’s engagement, creativity, and readiness to navigate the complexities of modern challenges. A stimulating learning environment and the teacher's role as a facilitator are essential components in supporting children's active knowledge construction. Although implementation varies across institutions, these learning strategies are generally perceived as effective, despite ongoing challenges such as limited teaching media, technological access, and teacher competencies. This transformation reflects a necessary adaptation by RA institutions to remain relevant and to equip children with critical thinking, social, and creative skills needed in today’s world. This study offers practical contributions to the development of early childhood learning models based on constructivism that are responsive to contemporary challenges and relevant to early childhood education policy in Indonesia.